1996
DOI: 10.1037/h0094452
|View full text |Cite
|
Sign up to set email alerts
|

Outline for a theory on the nature and functions of dreaming.

Abstract: Based on dreams after trauma and other recent research a view of the nature of dreaming is developed along the following lines. Dreaming makes connections more broadly than waking in the nets of the mind. Dreaming avoids the "central" rapid input-to-output portions of the net and the feed-forward mode of functioning; it makes connections in the further out regions (further from input/output) and in an auto-associative mode. Dreaming produces more generic and less specific imagery. Dreaming cross-connects. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
170
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(185 citation statements)
references
References 37 publications
8
170
0
7
Order By: Relevance
“…Of course 'real' memory fragments can also appear in the dream, but a new narrative, a new context will provide the guideline for the dream. Neuroimaging studies (MAQUET et al 2000) and phenomenological investigations of the content and structure of dreams (HARTMANN 1996;KAHN et al 2002) suggest that in the hyperassociative quasi-chaos of dreaming, emotions can be the main organizers. Accordingly, the core emotional concerns of the dreamer, conscious and unconscious affective patterns, can be the deep structure of the dream (NIELSEN & STENSTROM 2005).…”
Section: Dream Images and Memoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course 'real' memory fragments can also appear in the dream, but a new narrative, a new context will provide the guideline for the dream. Neuroimaging studies (MAQUET et al 2000) and phenomenological investigations of the content and structure of dreams (HARTMANN 1996;KAHN et al 2002) suggest that in the hyperassociative quasi-chaos of dreaming, emotions can be the main organizers. Accordingly, the core emotional concerns of the dreamer, conscious and unconscious affective patterns, can be the deep structure of the dream (NIELSEN & STENSTROM 2005).…”
Section: Dream Images and Memoriesmentioning
confidence: 99%
“…According to the neurocognitive model of the new dreamt contexts of intense emotional memories can serve the role of fear-extinction, while others emphasise that the associative enriching and the integration of the emotional memories into a broader self-centered, semantic network is the 'royal road' for emotional regulation (HARTMANN 1996;CARTWRIGHT et al 2006;STICKGOLD 2002;SIMOR 2007). Whichever mechanism is responsible for the emotional regulation, possibly both, research based evidences suggest that creating new contexts for frightening dreams may facilitate the improvement of waking affect.…”
Section: Dreams and Emotional Regulationmentioning
confidence: 99%
“…Many researchers have, on the basis of such results, suggested that 6 waking-life concerns may be preferentially incorporated into dreams (e.g. Davidson, Lee-Archer & Sanders, 2005;Domhoff, Meyer-Gomes & Schredl, 2006;Hartmann, 1996). On the other hand, other studies have found that independent judges were not able to match either pre-sleep thoughts or significant concerns to dream material (Roussy, 2000;Roussy et al, 1996), and some aspects of dreams in content analysis studies do not relate to participants' concerns, such as guns and kittens for one participant (Domhoff, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, evidence suggests that dreams facilitate 'mastery' over affectively arousing memories (Breger, 1967;Koulack, 1993;Wright & Koulack, 1987); emotional experiences are dreamt of repetitively until they are resolved (Hartmann, 1998); and dreams may enable the amelioration of emotions attached to waking-life experiences (Hartmann, 1996;Walker & van der Helm, 2009), perhaps particularly for fear emotions (Levin & Nielsen, 2007Levin et al, 2010;Nielsen & Lara-Carrasco, 2007). Another interpretation of the results could come from the emotional memory consolidation theory of sleep and dreaming, which is related to, but slightly different from, the emotion-processing theory.…”
mentioning
confidence: 99%
“…It has been shown that certain types of experiences are more likely to be incorporated into dreams than others, such as emotional experiences (Horton, Smith & Proctor, 2011;Malinowski & Horton, under review (a); Schredl, 2006), and this may indicate that dreams serve an emotional-processing (e.g. Hartmann, 1996;Walker & van der Helm, 2009) or emotional memory assimilation (Malinowski & Horton, in prep. ) function.…”
Section: Introductionmentioning
confidence: 99%